Response of Grafted Tomato (Solanum lycopersicum) to Herbicides. (December 2015) - Chaudhari, Sushila; Jennings, Katherine M.; Monks, David W.; Jordan, David L.; Gunter, Christopher C.; Louws, Frank J.
Abstract : Tomato grafting has gained increased attention in the United States as an alternative to methyl bromide to control soilborne pests and diseases. Although several herbicides are registered in tomato production, a lack of information exists on the effect of herbicides on grafted tomato. Greenhouse and field experiments were conducted to determine herbicide tolerance of grafted tomato. In greenhouse experiments, halosulfuron (27, 54, and 108 g ai ha −1 ), metribuzin (280, 560, and 1, 120 g ai ha −1 ), and S -metolachlor (1, 070, 2, 140, and 3, 200 g ai ha −1 ) were applied posttransplant to nongrafted 'Amelia' and Amelia scion grafted onto 'Maxifort' or 'RST-04-106-T' tomato rootstocks. Although herbicide injury was observed, no differences were observed in grafted and nongrafted tomato response including visible injury assessments, plant height, and fresh weight. Tomato injury at 3 wk after herbicide application increased from 3 to 12, 1 to 87, and 0 to 37% as rate of halosulfuron, metribuzin, and S -metolachlor increased, respectively. In field experiments under plasticulture, herbicides applied pretransplant included fomesafen (280 and 420 g ai ha −1 ), halosulfuron (39 and 54 g ha −1 ), metribuzin (280 and 560 g ha −1 ), napropamide (1, 120 and 2, 240 g ha −1 ), S -metolachlor (800 and 1, 070 g ha −1 ), and trifluralin (560 and 840 g ai ha −1 ). Amelia was used as the scion and the nongrafted control. 'Anchor-T', 'Beaufort', or Maxifort tomato were used as rootstocks for grafted plants. Fomesafen, halosulfuron, napropamide, and trifluralin initially caused greater injury to grafted tomato than to nongrafted tomato regardless of rootstock (Anchor-T, Beaufort, or Maxifort). However, by 4 wk after treatment, all grafted and nongrafted plants had recovered from herbicide injury. A transplant type-by-herbicide interaction was not observed for yield, but grafted A-Maxifort tomato produced greater total and marketable yield than nongrafted Amelia tomato. Grafted tomato exhibited similar tolerance as nongrafted tomato for all herbicides applied post- and pretransplant.